An Innovative Anode Interface Combination for Perovskite Solar Cells with Improved Efficiency, Stability, and Reproducibility. Issue 8 (8th June 2022) - Meng, Wei; Xu, Junyi; Dong, Lirong; Zhang, Jiyun; Xie, Zhiqiang; Luo, Junsheng; Zhao, Baolin; Zhang, Kaicheng; Osvet, Andres; Heumüller, Thomas; Forberich, Karen; Halik, Marcus; et al.
Abstract : Rational design and engineering of top interface layers with combined properties of effective passivation, high thermal‐ and photo‐stability are effective methods to advance the commercialization of perovskite photovoltaics. Here, an innovative anode interface combination is developed based on alcohol‐dispersed poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) nanoparticles as the hole transport material and chlorobenzene‐dissolved trioctylphosphine oxide (TOPO) as the passivation agent. It is shown that instead of the commonly used 2D passivation ligands, TOPO‐passivated perovskite films exhibit greatly improved thermal stability. Furthermore, the passivation contributes to an enhanced carrier lifetime and reduced surface trap density, yielding an improvement in the quasi‐fermi‐level splitting of 57 meV. To maintain surface passivation during solution processing of further layers, it is necessary to develop a hole transport layer that can be processed from orthogonal solvents. P3HT nanoparticles formulated in alcoholic media fully meet this requirement, clearly benefitting from their high vertical conductivity and extremely low contact resistance with carbon electrodes. Based on this configuration, device efficiency of up to 18.4% is demonstrated for perovskite solar cells with fully solution‐processed carbon electrodes, along with significantly improved device stability and reproducibility. Abstract : Printed carbon‐electrode‐based perovskite solar cells are developed by using the combination of poly(3‐hexylthiophene nanoparticles and trioctylphosphine oxide. The poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) nanoparticles (NPs) dispersed in alcohol offer a cheap, effective, and stable hole transport layer that further retain the trioctylphosphine oxide (TOPO) passivation effect. The optimized perovskite solar cells exhibit promising device efficiency, excellent reproducibility, and device stability.